2014
DOI: 10.5808/gi.2014.12.2.64
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Molecular Interactions of Natural Inhibitors with HPV-16 E6 Oncoprotein through Docking Analysis

Abstract: Human papillomavirus (HPV) infection is the leading cause of cancer mortality among women worldwide. The life-threatening infection caused by HPV demands the need for designing anticancerous drugs. In the recent years, different compounds from natural origins, such as carrageenan, curcumin, epigallocatechin gallate, indole-3-carbinol, jaceosidin, and withaferin, have been used as a hopeful source of anticancer therapy. These compounds have been shown to suppress HPV infection by different researchers. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…All the compounds were found to inhibit strongly by completely occupying the active sites in the target protein (2r5h), in this study the inhibitors is occupied within the AA 50-60 of the L1 protein, which is situated in the DE-Loop of the HPV L1 proteın. Most of the ligands were found to be having polar contact with the receptor (2r5h).The best two docking results were zinc_33737268 (chicoric acid) with a binding energy of -8.7 kcal/mol which is lower than the binding energy reported for Wıthaferin A docked against HPV E6 protein in a study by Kumar et al (2014), though in the same study carrageenan showed a much lower binding energy when docked agaınst E6 protein, but the present study targeted the L1 protein which is a more conserved region, the L1 also has the heparin binding site in its loop, which plays important role in high risk HPV…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…All the compounds were found to inhibit strongly by completely occupying the active sites in the target protein (2r5h), in this study the inhibitors is occupied within the AA 50-60 of the L1 protein, which is situated in the DE-Loop of the HPV L1 proteın. Most of the ligands were found to be having polar contact with the receptor (2r5h).The best two docking results were zinc_33737268 (chicoric acid) with a binding energy of -8.7 kcal/mol which is lower than the binding energy reported for Wıthaferin A docked against HPV E6 protein in a study by Kumar et al (2014), though in the same study carrageenan showed a much lower binding energy when docked agaınst E6 protein, but the present study targeted the L1 protein which is a more conserved region, the L1 also has the heparin binding site in its loop, which plays important role in high risk HPV…”
Section: Resultsmentioning
confidence: 89%
“…Non-polar hydrogen were added to the docked ligands. For Lamarckıan genetic algorithm, a maximum number of 15 × 10 5 energy evaluations, 27,000 maximum generations, 0.02 gene mutation rate and 0.8 crossover rate were used [18]. Each ligands has had two hundred independent docking runs.…”
Section: Receptor-ligand Docking Using Pyrx Virtual Screening Softwarementioning
confidence: 99%
“…The potential explanation for the discrepancy in p53 expression after treatment in the HPV+ cell lines may lie with the agent’s ability to regulate viral oncoprotein expression. The comparable expression of p53 to control groups in the HPV+ cells upon treatment with curcumin may be due to curcumin’s ability to downregulate viral oncoprotein HPV‐E6, which has historically bound and inhibited p53 function via ubiquitination and degradation . However, metformin’s interactions with HPV viral oncoproteins are currently unknown and would require further investigation before any conclusions can be made.…”
Section: Discussionmentioning
confidence: 99%
“…The active site of the model was analyzed based on the docking interaction between the p53 and pRb binding site residues (12)(13)(14)(18)(19)(20) of HPV oncoproteins, and all natural ligands.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we already described the positive results of using curcumin, epigallocatechin-3-gallate (EGCG), jaceosidin (12)(13)(14), resveratrol (13,14), indole-3-carbinol, withaferin A (12,14), artemisinin, ursolic acid, ferulic acid, berberin, resveratrol, gingerol, and silymarin (14) as indications that these compounds are possible effective sources of cancer treatment. …”
Section: Introductionmentioning
confidence: 99%